Uji Kombinasi Dosis Biochar Tankos dan Kotoran Ayam untuk Perbaikan Kesuburan Tanah Sawah - Urai Suci Yulies; Rini Hazriani; Mulidi Maulidi (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2022)
Paddy is the main crop in the tidal land farming system. The use of tidal land, especially for rice plants, faces many obstacles, in general it has low fertility due to the lack of macronutrients N, P, K as well as high and varied agrophysical constraints. For this reason, in rice cultivation, Alluvial land needs ameliorant that is easy to obtain and cheap in price, to help increase Alluvial soil fertility in addition to N, P and K fertilizers. The research was carried out by taking soil samples in Sei Kakap in 2 different locations, and then the samples were analyzed at the Chemistry and Soil Fertility Lab of Faperta Untan. This study used a dose of empty fruit bunches (tankos) biochar and chicken manure with a ratio of 25% : 75%, 50% : 50% and 75% : 25%. The treatment was repeated 5 times, so there were 15 treatments. The design used is the completely randomized design. The results of the study explain that from the incubation experiment between biochar tankos, chicken manure, for 4 weeks the C/N ratio was <20%, besides that base saturation and CEC were higher than 2 weeks incubation, indicating that the use of organic biochar tankos + chicken manure with a ratio of 25:50 and 50:50 can increase the fertility of paddy fields.